The EU's effectiveness in the Eastern Mediterranean migration quandary: challenges to building societal resilience. Issue 7 (3rd October 2021) - Ozcurumez, Saime
ABSTRACT: Under what conditions does the EU contribute to the prevention of governance breakdown and violent conflict in areas of limited statehood and contested orders by fostering societal resilience? This study seeks answers to this question by examining the EU's effectiveness in fostering societal resilience in Jordan, Lebanon, and Turkey while they have coped with risks emerging from cross-border mobility, mass influx, and prolonged stays of the forcibly displaced due to the Syrian crisis since 2011. The study argues that the EU has been constrained in building societal resilience. The findings suggest that the EU's effectiveness is limited by context-specific social, political, and economic risks in host countries; divergence among policy actors' often contradictory preferences; and the impact of the EU's policies in outsourcing management of forced displacement. The study concludes that the EU needs to link the implementation of its short-term pragmatic programmes that primarily enable state resilience in crisis contexts with its long-term liberal vision for fostering high level societal resilience with democratic principles and institutions.